Shear bond strength of orthodontic brackets bonded with different curing methods - Bahnasi, Faisal Ismail; Mohammed Abdullah, Nagham; Abu-Hassan, Mohamed Ibrahim (Faculty of Dentistry, 2014)
To evaluate the effect of light-cure devices and curing times on the shear bond strength (SBS) of orthodontic brackets. Material and Methods: 60-extracted human premolars were divided into 6-groups of 10-teeth each and bonded with stainless-steel brackets by using 3M Unitek Transbond XT composite. Specimens were cured with halogen, LED and plasma arc lights with two different times for each. The specimens were subjected to shear force till debond with a crosshead speed of 1mm/min and tested after 5min. The stress was calculated and data were subjected to statistical analysis. One-way ANOVA and Dunnett T3 post hoc comparison test were used. There were no significant differences between the 6 groups (p < 0.05). Conclusions: all curing light methods with loading force after 5 min achieved SBS more than the normal range; therefore, arch wire can be inserted at the same visit using any of tested curing light device or curing time.